Implementasi Kebijakan Rencana Tata Ruang Wilayah Berbasis Prinsip Pembangunan Berkelanjutan - Cahya Adhy Laksana; Nur Sifa Ramadan; Ardi Sumawijaya; Haris Budiman (Uniku Law Review, 2025)
This study aims to analyze the implementation of the Regional Spatial Planning (RTRW) policy based on the principles of sustainable development and to identify the inhibiting and supporting factors in its implementation. This study uses a normative legal research method with a statute approach and a case approach, supported by a literature review based on laws and regulations, books, official documents, and previous research findings. The results indicate that the implementation of the RTRW policy plays a strategic role in supporting sustainable development through efficient land use regulation, environmental protection, and the integration of socio-economic aspects into the spatial planning process. However, the implementation of this policy still faces several obstacles such as conflicts of interest between parties, lack of coordination, and low public participation in the planning and decision-making process. Meanwhile, influential supporting factors include infrastructure development in accordance with the spatial plan and the improvement of regional economic sectors, such as mining, which impacts Regional Original Income (PAD). Based on the analysis, it is concluded that the successful implementation of the RTRW based on sustainable development depends heavily on the synergy between the government, the community, and the private sector in achieving a balance between economic growth, environmental preservation, and sustainable social welfare.